The Status of Females in the Islamic System of Inheritance: Focus on The Advantages They Have Over Males - Yaaqub A.A. Wakili; Abubakar Sabo Yusha’u; Ahmad Yahya (Fakultas Agama Islam Universitas Billfath, 2023)
This paper attempts to look at, as well as bring out the noble status that females have in the Islamic system of inheritance. The objectives are to bring into the open the just nature of this system of succession and enlighten those non-Muslim scholars who label it as anti-females on the various advantages which females have in the distribution of inheritance. The method employed by this paper is descriptive, where data is elicited through document analysis, in which primary materials on Islam, both published and unpublished, electronic and print are consulted. The result discovered by the paper is that female heirs, inherit as daughters, mothers, wives, etc., and also inherit at double or triple capacity. For instance, a female heir can inherit her husband both as his wife and as his mistress if the husband happened to be a slave and she bought him and emancipated him. Moreover, almost all the heirs of the first category (As-hab al-furud) who are considered first when the distribution is to take place are females. For, instance, uterine sister and uterine brother enjoy equal shares. Moreover, females could get not only equal but also twice, triple, or even quadruple the share of males. A case in point is where the heirs are the daughter, son’s daughter, full sister, and consanguine brother. The female heirs in this case exhaust the entire estate and exclude the consanguine brother who is a male